A Study on the Backfire Effect of Liquidity on Enterprise Profits-Based on Life Cycle Perspective - Quan Xiao (Journal of Frontier in Economic and Management Research, 2025)
The expansion strategy is an important tool for enterprises to achieve growth and transformation, but it may lead to a lack of liquidity and thus a rapid decline. Does liquidity have a backfire effect on profits and thus lead to enterprise decline? Based on the life cycle theory, the empirical study of 72 ST-listed companies in China from 2010 to 2020 shows that liquidity is significantly and positively correlated with profits during the expansion period and negatively correlated with profits during the recession period, and the effect becomes larger as the characteristics of enterprise life cycle change gradually. The study also shows that profit and liquidity risk do not necessarily follow the principle of equal increase or decrease in different periods, which provides a new path for enterprise to strengthen liquidity risk management.